Comparative Effects of Hibiscus rosa Flower Extract and Silymarin on Lead Acetate Induced Hepatotoxicity in Male Albino Rats (Journal of Fatima Jinnah Medical University, 2025)
Background: Lead, a pervasive pollutant, induces liver toxicity through oxidative stress, inflammation, and enzyme disruption. Hibiscus rosa-sinensis and silymarin possess hepatoprotective properties, mitigating oxidative damage, stabilizing hepatocyte membranes, and promoting liver regeneration. Objective of this study is to examine the protective effects of a combination of Hibiscus rosa-sinensis flower extract and silymarin against lead acetate-induced liver toxicity in male albino rats.Subjects and methods: An experimental animal study was conducted at PGMI and LGH, Lahore (July 2023–July 2024) after ethical approval. Fifty albino rats were divided into five groups: Group A (control) received distilled water, while Groups B–E were given 500 mg/kg lead acetate alone or with 300 mg/kg Hibiscus rosa-sinensis extract, 200 mg/kg silymarin, or both for 30 days. Body and liver weights, serum ALT, AST, and glutathione peroxidase levels were measured. Liver sections were analyzed using H&E and Masson’s Trichrome staining. Histological toxicity indicators included hepatic architecture, portal triad inflammation, and fibrosis, assessed via the Histology Activity Index (HAI). Hepatic lobules were classified as normal (0) or abnormal (1), portal triad inflammation was scored from 0 to 4, and fibrosis ranged from 0 (none) to 4 (cirrhosis). Data were recorded, stratified according to toxicity indicators, and analysed using SPSS 25, with significance set at p ≤ 0.05.Results: Lead exposure caused weight loss (180.7 ± 6.2 g), hepatomegaly (10.6 ± 0.7 g), and liver damage (ALT: 80.3 ± 12.3 U/L, AST: 164.4 ± 8.3 U/L, GPX: 76.3 ± 7.0 U/L, p < 0.05), indicating toxicity. Hibiscus rosa-sinensis and silymarin reduced these effects, with the combination (190.7 ± 8.1 g, 7.5 ± 0.5 g, ALT: 28.1 ± 3.9 U/L, AST: 60.9 ± 9.3 U/L, GPX: 124.4 ± 3.9 U/L) suggesting the hepatoprotective effect.Conclusion: The combination of Hibiscus rosa-sinensis flower extract and silymarin exhibited the strongest hepatoprotective effects against lead acetate-induced liver damage in male albino rats, effectively preserving body and liver weight, reducing ALT and AST levels, and restoring GPX levels more effectively than either treatment alone.
Keywords: Hibiscus Flower Extract; Silymarin; Lead Acetate-Induced Liver Toxicity; Albino Rats; Hibiscus rosa-sinensis